2020
DOI: 10.1186/s41687-020-00213-w
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparative study of child and caregiver responses to three software functions added to the Japanese version of the electronic Pediatric Quality of Life Inventory (ePedsQL) questionnaire

Abstract: Background: Patient-reported outcomes (PROs) refer to any report of the status of a patient's health condition, health behavior, or experience with healthcare directly from the patient, without interpretation of the patient's response by a clinician or any other external party. While many PROs, such as the Pediatric Quality of Life Inventory (PedsQL), were originally administered in paper-and-pencil format, these are now available as electronic versions (ePROs). Although ePROs might well have used the same str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Research is found in the literature aiming at the development of educational software for teaching nursing students in several areas, including pediatrics (13)(14) . However, most of these applications focuses on the use of assessment forms and tools, diagnostic support, and rehabilitation (15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%
“…Research is found in the literature aiming at the development of educational software for teaching nursing students in several areas, including pediatrics (13)(14) . However, most of these applications focuses on the use of assessment forms and tools, diagnostic support, and rehabilitation (15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%